Similar effects of high-intensity intervals and continuous endurance runs during the preparation period in high level football - Faude, O.; Schnittker, R.; Müller, F.; Schulte-Zurhausen, R.; Meyer, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Aerobic fitness in elite football players has received considerable scientific attention during the last decade. Mainly, two considerably different endurance training methods are used. These are, on the one hand, classical continuous endurance runs and, on the other hand, high-intensity intervals. Scientific data comparing these methods is lacking. The present study aimed at analysing performance effects of continuous endurance runs vs. high-intensity intervals during the preparation period in high level youth football teams. 5 youth teams from German professional clubs playing in the two highest divisions (2xU19, 1xU18, 2xU17; 16.5±1.1 yrs, 69.8±8.4 kg, 1.77±0.07 m) were randomly assigned to either a high-intensity (2 teams, N=22, HIT) or a continuous endurance training group (3 teams, N=40, CON). Endurance training was conducted on average two times a week over the 5-week preparation period. HIT consisted of 2x12-15 repetitions of 15-30 s high-intensity runs (125-140% of maximal lactate steady state velocity, MLSS, Stegmann et al. 1981, rest: 15-30 s), whereas CON included continuous endurance runs (80-95% MLSS for 30-60 min). Before and after the training period several performance tests were conducted: a multi-stage exercise test (GXT) to determine MLSS, a straight sprint test (5x30 m), an agility test (20 m course involving 6 turns) and vertical jump tests (drop jump, counter movement jump). Both groups significantly improved MLSS (HIT: +0.7 km/h, effect size (ES)=0.96, CON: +0.6 km/h, ES=0.74, p<0.001 for pre-post intra-group comparisons) as well as maximal velocity during GXT (+0.3 km/h each, p=0.002) with no significant interactions between groups (p>0.26). Whereas straight sprint times did not change, agility was slightly improved (p=0.03, ES=0.26). Vertical jumping height was significantly decreased (p<0.001, ES=0.26 to 0.59) and drop jump contact time was slightly enhanced (p=0.06). No significant group interactions were observed (p>0.25). The results of the present study suggest that continuous endurance runs and high intensity intervals induce similar improvements in endurance performance. In addition, both training programs have no different effects on speed and power abilities. The improvement in endurance capacity is within the range of values previously reported after a preparation period. As recently shown, high intensity intervals induce similar enzymatic and metabolic adaptations compared to continuous endurance exercise (Burgomaster et al. 2008) and, thus, the underlying changes in physiological processes may be similar for both training Methods: In conclusion, continuous endurance runs as well as high intensity intervals revealed similar effects in high level youth football players and, thus, may be used interchangeably in sports practice.